Experimental study on damage pattern caused on Malaysian made hollow blocks by guns of different calibers - Hor, Tze Bao; T. Nataraja Moorthy,; Rasyidi Harun,; Mohd Zahedi Daud, (Malaysian Society of Applied Biology, 2016)
Firearm and ballistics in an important area in forensic investigation. Among three ballistics, terminal ballistics plays a vital role in to solve the mystery in crime scenes. The present experimental study is aimed to study the damage pattern caused on Malaysian made hollow blocks by using various firearm. For the experimental study, firearms viz. 0.38 revolver, 9mm submachine gun, 9 mm semi auto pistol, 5.56 mm rifle and 7.62 mm rifle were used with varying ranges. The shooting experiment was conducted at Sungai Buloh shooting range by trained firearms experts, Polis Di Raja Malaysia, Bukit Aman. Kuala Lumpur. The entry and exit damages were analyzed and the result of the investigation provided promising result in determining the type of firearm and other useful information. The entry damages are found to be comparatively smaller than the exit damages in the hollow blocks. The long arms caused more damages on the hollow blocks comparatively than hand arms.